Bidirektionale Abbildung zwischen Geschäftsprozessmodellen und IT-Kommunikationssystemen - Keuter, Björn (KIT Scientific Publishing, 2014)
How can people with different knowledge and experience use process models in the digital communication and at the same time how can they receive system support through the described processes? This question is solved by a mutual transformation based on natural language which is illustrated with practical examples. Thus, more widespread workflows can be implemented by incorporating system boundaries that were previously hard to overcome.